Effects of Hydrolysis and Digestion in Vitro on the Activity of Bovine Plasma Hydrolysates as Inhibitors of the Angiotensin I Converting Enzyme (2014)
ABSTRACT: The angiotensin I-converting enzyme (ACE) inhibiting activity of bovine plasma hydrolyzates obtained by Alcalase 2.4 L at different degrees of hydrolysis (DH) was evaluated. For the evaluation of ACE inhibition (ACEI), HippurylHis-Leu was used as substrate and the amount of hippuric acid liberated by non-inhibiting ACE was determined by spectrophotometry at 228 nm. The results showed that the enzymatic hydrolysis increased the ACEI activity as compared with the un-hydrolyzed plasma. The highest activity was onbtained with a DH of 6.7%. The peptide fractions with the maximum activity were isolated using ultrafiltration membranes, ion exchange chromatography and high performance liquid chromatography on reverse phase (RP-HPLC). The fraction with highest ACEI activity, showed an IC50 of 0.18 mg/mL and contained peptides with sequences AGATGVTISGAG, YSRRHPEYAVS, Q(K)AW and L(l)I(I)VR, which were determined by MALDI-TOF-TOF. It was also found that after submitting such fraction to digestive conditions in vitro, the ACEI activity remained constant.